Bringing critical literacy into tertiary EFL reading class - Setyaningsih, Endang (Indonesian Journal of Applied Linguistics, 2019)
Critical literacy (CL) is an area that remains under-researched regardless of the growing acknowledgement on its importance. Previously published works on CL have provided depictions of classroom implementations but they appeared to be lacking a guiding framework thus tended to be haphazard. This study addressed the gap by exploring the implementation of CL using a prototype model that combines the Four Resources Framework (FRF) as a theoretical frame and Survey, Question, Read, Recite, and Review (SQ3R) as a working model. The study aims at uncovering how CL could be infused into regular EFL Reading class using the model and how students developed their CL. The investigation involved 39 university students in Indonesia. The data were collected using multiple methods: observation, tests, interview, artifact, and questionnaire. Quantitative and qualitative data were concurrently analyzed by using statistical pack and interactive model, respectively. The study confirmed that questions and materials played key roles in turning a conventional Reading class into a CL class. Having exposed to critical questions, the students indicated progress in their practice as text users and text analysts. The analysis revealed that the students at differing baselines addressed the four roles differently in terms of the extent and consistency. Students with high proficiency tended to be more consistent in addressing the text user and text analyst roles either individually or as part of the group. In contrast, students with lower proficiency indicated inconsistent engagement with the two roles, particularly in individual work. Generally, the students’ ability to build critical stance to text was also determined by the complexity of the material. The easier the text was comprehended, the more critical the students were toward the text. The study suggests that it be necessary to include explicit teaching and sufficient provision of time in CL teaching to produce an automated critical response to texts.